(untitled) (Ágora de Heterodoxias, 2019)
This article compiles the experiences of students group who participated in an internationalization research experience supported by the leadership of the Research Program for the Promotion of Networking (ProRed) and the Student Mobility Commission of CONARE, Universidad Estatal a Distancia de Costa Rica. During this research and through a qualitative and explanatory methodological approach, an instrument was applied to the entire population that was mobilized during 2015 and 2016. A taxonomy of research competencies was proposed according to Alles (2005). As a result, a series of benefits for students are highlighted, as well as the development of specific skills